Biochemical characterization of recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) protein from Leucaena leucocephala was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. Optimum pH for forward and reverse reaction was found to be 6.5 and 7.8 respectively. The enzyme was most stable around pH 6.5 at 25 degrees C for 90 min. The enzyme showed k(cat)/k(m) for feruloyl, caffeoyl, sinapoyl, coumaroyl CoA, coniferaldehyde and sinapaldehyde as 4.6, 2.4, 2.3, 1.7, 1.9 and 1.2 (x10(6) M-1 s(-1)), respectively, indicating affinity of enzyme for feruloyl CoA over other substrates and preference of reduction reaction over oxidation. Activation energy, E-a for various substrates was found to be in the range of 20-50 kJ/mol. Involvement of probable carboxylate ion, histidine, lysine or tyrosine at the active site of enzyme was predicted by pH activity profile. SAXS studies of protein showed radius 3.04 nm and volume 49.25 nm(3) with oblate ellipsoid shape. Finally, metal ion inhibition studies revealed that Ll-CCRH1 is a metal independent enzyme. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Activation energy; Cinnamoyl CoA esters; Cinnamoyl CoA reductase 1; SAXS; stability

Bacopa monniera recombinant mevalonate diphosphate decarboxylase: biochemical characterization - Shakeel Abbassi; Vishwakarma, Rishi K.; Patel, Parth; Kumari, Uma; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate diphosphate decarboxylase (MDD; EC 4.1.1.33) is an important enzyme in the mevalonic acid pathway catalyzing the Mg2+-ATP dependant decarboxylation of mevalonate 5-diphosphate (MVAPP) to isopentenyl diphosphate (IPP). Bacopa monniera recombinant MDD (BmMDD) protein was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. K-m and V-max for MVAPP were 144 mu M and 52 U mg(-1) respectively. The values of turnover (k(cat)) and k(cat)/K-m, for mevalonate 5-diphosphate were determined to be 40 s(-1) and 2.77 x 10(5) M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found to be 30 s(-1) and 2.20 x 10(4) M-1 s(-1), respectively. pH activity profile indicated the involvement of carboxylate ion, lysine and arginine for the activity of enzyme. The apparent activation energy for the BmMDD catalyzed reaction was 12.7 kJ mol(-1). Optimum pH and temperature for the forward reaction was found to be 8.0 and 45 degrees C. The enzyme was most stable at pH 7 at 20 degrees C with the deactivation rate constant (K-d(*)) of 1.69 x 10(-4) and half life (t(1/2)) of 68 h. The cation studies suggested that BmMDD is a cation dependant enzyme and optimum activity was achieved in the presence of Mg2+. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mevalonate diphosphate decarboxylase; pH activity profile; Phylogenetic analysis; stability

Biochemical characterization of recombinant mevalonate kinase from Bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Sonawane, Prashant; Shakeel Abbassi; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate kinase (MK; ATP: mevalonate 5-phosphotransferase; EC 2.7.1.36) plays a key role in isoprenoid biosynthetic pathway in plants. MK catalyzes the phosphorylation of mevalonate to form mevalonate-5-phosphate. The recombinant BmMK was cloned and over-expressed in E. coli BL21 (DE3), and purified to homogeneity by affinity chromatography followed by gel filtration. Optimum pH and temperature for forward reaction was found to be 7.0 and 30 degrees C, respectively. The enzyme was most stable at pH 8 at 25 degrees C with deactivation rate constant (Kd*) 1.398 x 10(-4) and half life (t(1/2)) 49 h. pH activity profile of BmMK indicates the involvement of carboxylate ion, histidine, lysine, arginine or aspartic acid at the active site of enzyme. Activity of recombinant BmMK was confirmed by phosphorylation of RS-mevalonate in the presence of Mg2+, having K-m and V-max 331.9 mu M and 719.1 pKat mu g(-1), respectively. The values of k(cat) and k(cat)/K-m for RS-mevalonate were determined to be 143.82 s(-1) and 0.43332 M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found 150.9 s(-1) and 1.023 M-1 s(-1). The metal ion studies suggested that BmMK is a metal dependent enzyme and highly active in the presence of MgCl2. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bacopa monniera; Enzyme kinetics; Mevalonate kinase; stability

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Role of base fluid on the thermal conductivity of oleic acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (COLLOIDS AND SURFACES A-PHYSICOCHEMICAL AND ENGINEERING ASPECTS, 2017)
Thermal conductivity enhancement of nanofluids of oleic acid coated magnetite nanoparticles dispersed in four different base fluids (toluene, xylene, mesitylene, kerosene) is studied to understand the role of the solvent (base fluid). From the correlation of the thermophysical properties of the base fluid with the thermal conductivity of the corresponding nanofluid, it is found that the nanofluid with the base fluid of lower intrinsic thermal conductivity and dielectric constant shows relatively larger enhancement in the thermal conductivity. A linear increase in the thermal conductivity with increasing viscosity is observed for all four nanofluids studied. The concentration dependent thermal conductivity studies showed enhancement only above a particular concentration, within the sensitivity of the measurement, and this critical concentration is different for the different nanofluids. The nanofluid with kerosene showed the lowest critical concentration for thermal conductivity enhancement compared to the other nanofluids. The difference between the experimental thermal conductivity and the calculated value using the Maxwell model is found to depend on the critical concentration. By assuming the critical concentration as the zero concentration, it is found that all the studied nanofluids almost follow the Maxwell model of thermal conductivity. Thus, for the dispersions of the same oleic acid coated magnetite nanoparticles, the base fluid affects the critical concentration for thermal conductivity enhancement, probably due to the interfacial effects arising from the surfactant-solvent interactions.
Keywords: Brownian-Motion; Enhancement; Heat-transfer Characteristics; Magnetic nanofluids; Maxwell model; Nanoparticles; Particle Migration; Size; stability; Suspension; Temprature; Thermal conductivity; Thermophysical properties; transport mechanism; viscosity

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas

Non-isothermal analysis of extrusion film casting using multi-mode Phan-Thien Tanner constitutive equation and comparison with experiments - Chougale, Sanket; Rokade, Dhammaraj; Bhattacharjee, Tanushree; Pol, Harshawardhan; Dhadwal, Renu (Rheologica Acta, 2018)
Extrusion film casting (EFC) is an industrially important process which produces thousands of tons of polymer films, sheets, and coating used for various industrial as well as household applications. In this paper, we focus on an instability which occurs during certain polymer processing operations operating under predominantly elongational flow, such as extrusion film casting and fiber spinning. This instability, called the draw resonance, occurs in the form of sustained periodic fluctuations in the film dimensions. It appears when the process goes beyond the critical line speed of the EFC process. In this work, a conventional linear stability analysis is carried out for nonisothermal EFC process to determine the onset of the draw resonance. The polymer rheology is modeled by the Phan-Thien Tanner (PTT) multi-mode constitutive equation. For the implementation, a conventional shooting method approach is used. Extrusion film casting experiments were also carried out using a conventional linear low-density polyethylene (LLDPE) by varying process parameters such as draw ratio and aspect ratio, to observe the effect on the stability of the process. Linear stability analysis results under non-isothermal conditions are compared and validated with existing results from literature and with our own experimental data. This work displays the effect of multiple relaxation modes as well as the temperature influence on the stability of EFC process. Finally, results also indicate that the temperature highly affects the stability of the EFC process and cannot be ignored from modeling of EFC process.
Keywords: Deborah number; Draw resonance; Film extrusion; Multi-mode; Nonisothermal; stability

Controlling draw resonance during extrusion film casting of nanoclay filled linear low-density polyethylene: an experimental study and numerical linear stability analysis - Rokade, Dhammaraj; Chougale, Sanket; Patil, Prashant; Bhattacharjee, Tanushree; Gawande, Dnyaneshwar; Pol, Harshawardhan; Dhadwal, Renu (Journal of Plastic Film & Sheeting, 2021)
Commercially important extrusion film casting (EFC) processes for manufacturing plastic films or sheets are hampered by several instabilities that severely limits their productivity. In this research we focussed on one important instability: the draw resonance that occurs during the EFC process mainly under extensional flow conditions. Draw resonance is the sustained periodic oscillations in the film dimensions, notably film width and thickness, when the process operates beyond a critical draw ratio (CDR). In this research our goal was to reduce this draw resonance instability by incorporating well dispersed nanoclay fillers in a base polymeric resin (such as a linear low density polyethylene - LLDPE) to determine how these nanocomposite (NC) formulations can prevent or reduce the draw resonance defect. EFC experiments were conducted on the base resin and on the NC formulations under non-isothermal conditions to determine the onset of the draw resonance experimentally. Conventional linear stability analysis was performed to determine the onset of the draw resonance defect numerically. Numerical predictions for the onset of draw resonance were in qualitative agreement with our experimental data. Our results showed that incorporating appropriate nanoclay concentrations in a base polymeric resin indeed enhanced the EFC process stability for those polymer formulations and thus can have important economic implications for processors.
Keywords: Draw resonance; extensional strain hardening; Extrusion; Film; hydrodynamic interactions; Nanoclay; Nanocomposites; Polyethylene; Rheology; stability

Post-refolding stability considerations for optimization of in-vitro refolding: L-asparaginase as a case study - Mihooliya, Kanti Nandan; Nitika, Nitika; Bhambure, Rahul; Rathore, Anurag S. S. (Biotechnology Journal, 2023)
BackgroundL-Asparaginase is an essential enzyme for the food and biopharmaceutical industry. The stability, however, of L-asparaginase is widely known to be an issue. Commercial manufacturing of any biopharmaceutical involves hold-ups during processing, and can result in product loss if stability is an issue, as is the case with L-asparaginase. This interplay of product intermediate stability and process design is the focus of this investigation. Methods and ResultsIn this study, we propose a strategy to simultaneously increase the refolding yield and stability of refolded L-asparaginase so as to improve overall process yield. Using one variable at a time (OVAT) experiments, urea (6 M), solubilized inclusion bodies (15 mg/ml), refolding method (step dilution), and pH (8.6) were identified as significant process parameters. A design of experiment (DOE)-based optimization was then performed for the refolding step. The net outcome was more than a three-fold increase in enzyme recovery (i.e., 4.90 IU/ml) compared to unoptimized conditions (i.e., 1.26 IU/ml). Further, the L-asparaginase process intermediate was found to be stable for more than a week at room temperature and 2-8 degrees C, while the unoptimized sample was stable at 2-8 degrees C but did not show any activity at room temperature after 72 h. ConclusionsThe current study elucidates how process intermediate stability needs to be given due consideration during process optimization, particularly for products such as L-asparaginase which are labile.
Keywords: design of experiment; L-asparaginase; refolding; stability

Pathological mutations D169G and P112H electrostatically aggravate the amyloidogenicity of the functional domain of TDP-43 - Pillai, Meenakshi; Patil, Anjali D.; Das, Atanu; Jha, Santosh Kumar (ACS Chemical Neuroscience, 2024)
Aggregation of TDP-43 is linked to the pathogenesis of many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Notably, electrostatic point mutations such as D169G and P112H, located within the highly conserved functional tandem RNA recognition motif (RRM) domains of the TDP-43 protein (TDP-43tRRM), have been identified in diseased patients as well. In this study, we address how the electrostatic mutations alter both the native state stability and aggregation propensity of TDP-43tRRM. The mutants D169G and P112H show increased chemical stability compared to the TDP-43tRRM at physiological pH. However, at low pH, both the mutants undergo a conformational change to form amyloid-like fibrils, though with variable rates-the P112H mutant being substantially faster than the other two sequences (TDP-43tRRM and D169G mutant) showing comparable rates. Moreover, among the three sequences, only the P112H mutant undergoes a strong ionic strength-dependent aggregability trend. These observations signify the substantial contribution of the excess charge of the P112H mutant to its unique aggregation process. Complementary simulated observables with atomistic resolution assign the experimentally observed sequence-, pH-, and ionic strength-dependent aggregability pattern to the degree of thermal lability of the mutation site-containing RRM1 domain and its extent of dynamical anticorrelation with the RRM2 domain whose combination eventually dictate the extent of generation of aggregation-prone partially unfolded conformational ensembles. Our choice of a specific charge-modulated pathogenic mutation-based experiment-simulation-combination approach unravels the otherwise hidden residue-wise contribution to the individual steps of this extremely complicated multistep aggregation process.
Keywords: amyloid fibrils; conformational changes; disease mutations; electrostatics; Protein aggregation; stability

Tensile nanostructured hierarchically porous non-precious transition metal-based electrocatalyst for durable anion exchange membrane-based water electrolysis - Singh, Kailash; Selvaraj, Kaliaperumal (Journal of Colloid and Interface Science, 2024)
Electrochemical water electrolysis is a promising method for sustainable hydrogen production while transiting towards hydrogen economy. Among many, the Anion Exchange Membrane (AEM) based water electrolyzer is an emerging yet potentially affordable technology on maturity for producing large-scale hydrogen accommodating the usage of Non-Platinum Group Metal (non-PGM) based inexpensive electrocatalysts. Herein, we demonstrate the excellent performance of a bifunctional Nickel Copper Phosphide-Nickel sulphide (NCP-NS) electrocatalyst with a unique tensile nanostructure obtained via a facile, controlled ambient galvanic displacement route. An AEM electrolyzer with a larger active area of 10 cm(2) stacked with the symmetric NCP-NS electrodes and a membrane demonstrates scalability with a requirement of a mere 1.66 V to reach a current density of 10 mA cm(-2). The nickel-copper phosphide boosts the kinetics of charge transfer between the electrode and electrolyte interface, while a unique combination of a few nickel sulphide phases present in the catalyst provides sufficiently appropriate active sites for the overall water electrolysis. For the first time, we report a room temperature performance of similar to 230 mA cm(-2) at 2 V for a non-PGM-based bifunctional electrocatalyst with exceptional durability for over 300 h of operation in an AEM water electrolyser with a retention rate of 95 %-97 % at a current density range of 80-800 mA cm(-2).
Keywords: AEM electrolyzer; Bifunctionality; Electrodeposition; Non-PGM based Electrocatalyst; stability

High performance and enhanced stability of Mn-Co3V2O8 coral-like structure for supercapacitor applications - Venkatesan, Sethuraman; Rajkumar, Palanisamy; Radhika, Govindaraju; Iyer, Maalavika S.; Manigandan, Ramadoss; Rajaiah, Dhilip Kumar; Radhakrishnan, S.; Raman, Sasikumar; Marimuthu, Senthilkumaran; Kim, Jinho (ACS Applied Energy Materials, 2025)
This study explores Mn-doped Co3V2O8 as a promising electrode material for high-performance supercapacitors. Mn doping significantly enhances the electrochemical properties of Co3V2O8, resulting in improved specific capacitance and cycling stability. Structural characterization reveals a coral-like morphology that increases the active sites and facilitates efficient charge transport and ion diffusion. Electrochemical tests show an impressive specific capacitance of 2352 F g(-1) in 2 M KOH at 1 A g(-1). For the assembled MCV5//AC asymmetric supercapacitor device, it has a high capacitance retention of 87.6% and a high Coulombic efficiency of 96% over 5000 cycles. The developed asymmetric MCV5/AC supercapacitor device achieved an energy density of 45 Wh kg(-1) and a power density of 750 W kg(-1). These findings establish Mn-doped Co3V2O8 as a durable and efficient electrode material, offering valuable insights into the relationship between the morphology and electrochemical performance. This work provides a foundation for the development of advanced materials for sustainable energy storage applications
Keywords: Co3V2O8; Electrode material; Energy storage; stability; supercapacitor

Platinum-free electrocatalysts based on electrodeposited Co-Mn-Ni alloys for efficient electrocatalytic alkaline water splitting - Chandran, M. Athira; Dutta, Pritha; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (ACS Applied Energy Materials, 2025)
The development of a Pt-free electrocatalyst for efficient and stable water splitting is crucial for the commercialization of green hydrogen production. A low-cost electrocatalyst with good hydrogen and oxygen evolution activities (HER and OER, respectively) displaying long durability is the first step in this direction, and if the catalyst can be synthesized via an easy, convenient, and scalable procedure, that would be an added advantage. Multicomponent alloys, with their tunable compositions and abundant active sites, present a promising solution in this direction. Herein, a cost-effective CoMnNi (CMN) alloy is synthesized via electrodeposition and with optimized composition by tuning the electrolyte concentration and deposition potential to enhance electrocatalytic performance. The resulting single-phase alloy exhibits a high electrochemical surface area with an average particle size of similar to 4 nm, demonstrating excellent hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities in 1 M KOH, with overpotentials of 121 mV at -10 mA cm-2 and 285 mV at 20 mA cm-2, respectively. Moreover, the catalyst exhibits remarkable stability, sustaining 100 h of operation at 100 mA cm-2. The CMN alloy also performs efficiently under harsh conditions, including 6 M KOH and alkaline seawater, in both symmetric and asymmetric cell configurations. This work highlights the potential of multicomponent alloys as durable, high-performance electrocatalysts for scalable water splitting, paving the way for sustainable hydrogen production.
Keywords: alkaline seawater; electrocatalysis; Electrodeposition; hydrogen evolution reaction(HER); multicomponentalloy; oxygen evolution reaction (OER); stability; watersplitting

Nanostructured Fe-ZIF supported on ni foam as electrocatalyst for the oxygen evolution reaction - Prakash, Satya; Nagar, Harsha; Singh, Archana (ACS Applied Nano Materials, 2026)
Developing and constructing highly stable and active electrocatalysts for the water oxidation or oxygen evolution reaction (OER) remains critical for achieving efficient water splitting. Herein, we report the in situ transformation of iron-cobalt hydroxycarbonate directly grown on nickel foam (NF) into nanostructured Fe0.2ZIF(67 + 9)/NF via a ligand-engineering strategy using a solvothermal approach. Post-OER characterization reveals a slight increase in oxygen content, suggesting surface reconstruction during electrochemical operation. The obtained Fe0.2ZIF(67 + 9)/NF exhibits outstanding catalytic performance, revealed in a low overpotential value of only 250 mV to reach the current density of 50 mA cm-2 with a small Tafel slope of 60 mV dec-1, indicative of accelerated reaction kinetics and favorable charge-transfer characteristics. Moreover, the electrochemically active surface area (ECSA) taken before and after 100 C-V cycles shows a 6.5% increase, indicating a structural activation, which is supported by an enhancement of anodic charge by about 13% as compared to Fe0.2ZIF-9/NF. Furthermore, just a 2 mV increase in potential after a 24 h chronopotentiometry test and a 37 mV decrease to sustain 25 mA cm-2 current density depicted the high stability and surface activation in Fe0.2ZIF(67 + 9)/NF. The enhanced catalytic efficiency is further supported by activation energy calculations, confirming improved reaction energetics. Moreover, from the Tafel slope analysis, the K H/K D ratio was calculated, which comes to about 0.42, suggesting a strong inverse kinetic isotopic effect, indicating that proton transfer is not involved in the rate-determining step and that O-H bond cleavage does not control the reaction kinetics. Overall, this study highlights ligand engineering as an effective strategy to regulate structural transformation and surface reconstruction, offering a promising pathway for the rational design of advanced nanostructured ZIF-based electrocatalysts for efficient and durable water oxidation.
Keywords: Activation energy; electrocatalyst; hydroxycarbonate; KIE; stability; ZIF